Comparison of DNA Quantity Extracted from Formalin and Ethanol Fixed Tissues - Chalermwong, Piangjai; Seelanan, Parinya; Sinloyma, Patchara (Asian Health, Science and Technology Reports, 2022)
This study was performed to compare DNA quantity extracted from the cerebrum part of porcine brain tissues preserved in 10% formalin or 95% ethanol, for 8 weeks. A sample was collected and DNA extracted at least once a week using a QIAamp DNA FFPE Tissue Kit. The Qubit 4 Fluorometer was then used for DNA quantification and to study the association between preservation duration and fixatives to evaluate the effect of two factors on DNA quantity, which can support forensic officers in choosing the most effective fixative to preserve tissues for DNA testing. The results showed that the concentration of extracted DNA from the tissues preserved in 95% ethanol was significantly higher than in the 10% formalin-fixed tissues. Moreover, DNA concentration from tissues preserved in 10% formalin significantly decreased after one week of preservation, while no significant difference was observed between DNA concentration in 95% ethanol fixed tissues after preservation. In addition, the negative correlation between preservation duration and DNA quantity in both 10% formalin and 95% ethanol fixed tissues was observed. It can be described that extracted DNA concentrations from tissues preserved in 10% formalin and 95% ethanol were decreased when the preservation time increased. However, we found that DNA concentration from 10% formalin-fixed tissues reduced than tissues preserved in 95% ethanol by 40%. Therefore, it can be concluded that 95% ethanol has better preservation properties and can be an alternative for a suitable method to preserve DNA from brain tissues compared to the 10% formalin solution.